Microfluidic Model for Evaluation of Immune Checkpoint Inhibitors in Human Tumors. Issue 11 (6th May 2019) - Beckwith, Ashley L.; Velásquez‐García, Luis F.; Borenstein, Jeffrey T.
Abstract: Presented is the first demonstration of real‐time monitoring of the response of resident lymphocyte populations in biopsied tumor tissue to immunotherapeutic agents in a perfused tumor microenvironment. This technology comprises a microfluidic tumor trapping device constructed from a novel 3D‐printed, transparent, noncytotoxic substrate. The 3D‐printed device sustains viability of biopsied tissue fragments under dynamic perfusion for at least 72 h while enabling simultaneous administration of various drug treatments, illustrating a useful tool for drug development and precision medicine for immunotherapy. Confocal microscopy of the tumor tissue and resident lymphocytes in the presence of fluorescent tracers provides real‐time monitoring of tumor response to various immunotherapies. Devices are additively manufactured in Pro3dure GR‐10 (i.e., a relatively new, high‐resolution stereolithographic resin with properties suitable for biomedical applications), allowing integration of a set of finely featured functional components into a monolithically constructed platform. The presented platform comprises a new methodology for modeling and analyzing tumor response for the improved prediction of patient‐specific immunotherapy efficacy. It is acknowledged that this is the first report of human tumor fragments cultured in a dynamic perfusion system capable of testing the effect of circulating immune checkpoint inhibitors on resident tumor‐infiltrating lymphocytes. Abstract : Three‐dimensional printing enables the fabrication of monolithic, microfluidic platforms which facilitate biomedical analyses, substantially reducing platform construction times, enabling complex device geometries, and improving usability. The presented microfluidic device is the first dynamic system investigating the effect of immune checkpoint inhibitors on resident lymphocytes in human tumor fragments, ultimately to predict drug response and guide effective cancer therapy administration.